Pan-cancer analysis identifies CD155 as a promising target for CAR-T cell therapy - Xiaohong Liu; Yue Sun; Boxu Lin; Hao Xiong; Xinyue Lu; Binghe Tan; Chenglin Zhang; Mingyao Liu; Juliang Qin; Na Zhang; Bing Du (Genome Medicine)
Abstract Background Chimeric antigen receptor T (CAR-T) cell therapy has shown remarkable success in treating hematologic malignancies. However, its efficacy against solid tumors remains limited. One of the major challenges is the lack of specific tumor antigens. Therefore, the exploration and rational selection of novel tumor targets is urgently needed. In this study, we investigate the therapeutic potential of targeting CD155 in cancer by CAR-T cells. Methods The expression of CD155 was analyzed across various cancer types using data from The Cancer Genome Atlas (TCGA) and validated by tissue microarray analysis. The impact of CD155 on T cell mediated cytotoxicity was analyzed using CD155 over-expression or knockout tumor cells. Subsequently, second-generation CAR-T cells were constructed using either the extracellular domain (ECD) of TIGIT or an anti-CD155 scFv to evaluate their anti-tumor efficacy both in vitro and in vivo. Results We demonstrated that CD155 is specifically overexpressed across various cancer types and that its high expression is strongly associated with poor prognosis, as revealed by data from TCGA. Consistently, CD155 is significantly upregulated in clinical tumor tissues and in numerous cancer cell lines, while it is rarely expressed in normal tissues. Furthermore, CD155 expression is also significantly increased in granulocytes derived from cancer patients compared to those from healthy donors. Functionally, high CD155 expression significantly inhibits the release of cytotoxic factors from T cells, thereby functioning as an immune checkpoint that mediates tumor immune evasion. After comparison, the scFv based anti-CD155 CAR-T cells demonstrated stronger anti-tumor activity than ECD of TIGIT based CAR-T cells. Moreover, the scFv based CAR-T cells exhibited effective anti-tumor activity against multiple CD155+ solid and hematologic tumors both in vitro and in different xenograft mouse models. Conclusions Our study demonstrates that CD155 is selectively expressed in cancer cells while being rarely detected in normal tissues, and may serve as a promising pan-cancer target for CAR-T therapy. Targeting CD155 with CAR-T cells provides an effective approach to treating both solid and hematologic malignancies.